2021
DOI: 10.1007/s00062-021-01008-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Complications and Vessel Wall Imaging in COVID-19 Encephalopathy—A Pilot Study

Abstract: Background and Purpose Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with several complications of the central nervous system (CNS), including acute encephalopathy. Methods In this pilot study, we report a series of 39 patients (66.5 ± 9.2 years; 10.3% female) with acute encephalopathy, who underwent a standard brain magnetic resonance imaging (MRI) at 1.5 T during the acute sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…1d and Fig 2a–c; bilateral vertebral arteries in Fig. 3d) of the addressed study [ 1 ] resemble the appearance of high-resolution vessel wall images from our non-vasculitic cohort (Fig. 2a–c, Fig.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…1d and Fig 2a–c; bilateral vertebral arteries in Fig. 3d) of the addressed study [ 1 ] resemble the appearance of high-resolution vessel wall images from our non-vasculitic cohort (Fig. 2a–c, Fig.…”
supporting
confidence: 61%
“…with interest we read the study by Uginet et al. “Cerebrovascular Complications and Vessel Wall Imaging in COVID-19 Encephalopathy—A Pilot Study” [ 1 ]. They described the findings on high-resolution black blood vessel wall magnetic resonance imaging (MRI) at 1.5 T that was performed in 34 older patients (66.5 ± 9.2 years; 10.3% female) with coronavirus diseases 2019 (COVID-19) and acute encephalopathy in a retrospective observational study.…”
mentioning
confidence: 99%
“…Enhancements were also seen in left communicating ICA, proximal basilar artery, and left distal V4 VA, suggesting a multifocal or diffuse pattern of vasculopathy. VWI has been reported to detect vascular involvement in around 85% of cases of COVID-19 encephalopathy [ 13 ]. However, no significant correlation between infarction or hemorrhage with vessel wall enhancement was found.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng-Ching et al have shown that VWI not only helps in diagnosis of varicella vasculopathy, but also has an immense role in guiding treatment duration and assessing treatment response [ 11 ]. Role of VWI in diagnosing vasculopathy in COVID-19, herpes encephalitis, HIV encephalopathy, and HCV encephalopathy have also been described in literature [ 5 , 13 15 ]. In this study, we aim to assess vascular complications of various viral CNS infections using high-resolution VWI, which may help to better understand the pathophysiology of secondary viral vasculitis and can have impact on management protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated abnormal findings on MRI vessel wall imaging (VWI) in hospitalized COVID-19 patients [3,5]. In addition, there is evidence that VWI complements conventional luminal imaging by increasing the reader's sensitivity for the detection of abnormalities, as well as augment the characterization these abnormalities [6]. Here, we report a case of intracranial inflammatory vasculopathy well demonstrated by vessel wall imaging (VWI), coincident with middle cerebral artery stroke, in a patient with COVID-19 and minimal pulmonary symptoms.…”
Section: Introductionmentioning
confidence: 99%